Penanganan obstetri prolaps uterus pascapersalinan pada sapi Angus potong skala kecil - Rini Widyastuti; Muhammad Rosyid Ridlo (School of Veterinary Medicine and Biomedical Sciences, Bogor Agricultural University, 2026)
Postpartum uterine prolapse is a severe reproductive emergency in cattle that may result in hemorrhage, contamination, shock, and death if not treated promptly. This case report describes the successful management of uterine prolapse in a 5-year-old Angus beef cow maintained under a traditional smallholder farming system. The animal was found in lateral recumbency one day after calving, presenting with complete uterine prolapse and impaired standing ability. Clinical examination revealed a rectal temperature of 38.5 °C. Immediate treatment involved epidural-assisted manual repositioning of the prolapsed uterus, followed by vulvar retention suturing using a simple interrupted pattern. Adjunctive therapy included amoxicillin, vitamin B12, and an antihistamine. Clinical recovery was achieved without recurrence or post-treatment complications